If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + (-3) * x + 5 + (-6) * x = 0 Reorder the terms: -7 + 5 + -3x + -6x = 0 Combine like terms: -7 + 5 = -2 -2 + -3x + -6x = 0 Combine like terms: -3x + -6x = -9x -2 + -9x = 0 Solving -2 + -9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -9x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -9x = 0 + 2 -9x = 0 + 2 Combine like terms: 0 + 2 = 2 -9x = 2 Divide each side by '-9'. x = -0.2222222222 Simplifying x = -0.2222222222
| 0.18(y-8)+0.08y=0.06y-0.09(30) | | 6w-2w=44 | | 5(x+4)=3x-2(4) | | 5x^2-40+75=0 | | 0.50x+0.45(70)=0.25(114) | | -6(x-2)=3(x+14) | | 5/12+a=11/12 | | 20+n=1 | | 40t+55x= | | 1.5+0.3r=-4.2 | | 4-5k=-4k+7 | | 15y-3x=-6 | | a=400+(-80)(1-1) | | x+12=17-4x | | 160+0.25n=342.50 | | 6(3x-2)=3x+5x | | 10x-25=625 | | x/10-5/2+x=3x/5 | | 3n+1=5n+8 | | 4(m+3)=44 | | 2x+4259=210355 | | 2(x-8)=10 | | 9x+6y=18 | | -2y=4-6x | | 2(3x-1)=4x+5 | | 5(x+5)=64 | | 3(2f-6)+6=36 | | 3n+2(4n-5)-7+n= | | -6x+2x=3x | | x=6x^7+35x^6-169x^5-612x^4+1823x^3+1215x^2-2758x-980 | | 7x+31=91 | | 2x+3=3+2 |